Linear movement and habitat boundary response by butterflies in power line corridors - Linder, Axel (SLU/Dept. of Ecology, 2017)
Sweden’s semi-natural grasslands and pastures have decreased radically during the 1900s, leading to a loss of butterfly populations and species associated with these habitats. Butterfly conservation efforts therefore should be concentrated towards finding suitable habitats that can either replace or support these lost habitats. Power line corridors in Sweden are cleared of vegetation every eight years with controlled cutting every four years, creating a habitat at an early successional stage suitable as a habitat and for butterfly dispersal. This study was divided in to two parts. The first part focused on how the butterflies Aphantopus hyperantus and Coenonympha arcania responded to power line corridors as a habitat edge, while at the same time being compared to a forest edge, in central Sweden. No significant response to the power line corridor as an edge was found and equally no significant response towards the forest edge was found. Therefore, foraging butterflies can move freely in to power line corridors from suitable habitats, making conservation efforts easier. But since no significant response was seen on a less permeable unsuitable matrix, the forest edge, further studies may be needed to see if this is true for more species. The second part of the study focused on linear movement in power line corridors, were A. hyperantus, C. arcania and Melitaea athalia were studied in a mark-release-recapture study in central Sweden. Movement in the power line corridor was very similar to movement in wooded grassland, concerning ranges and patterns. The density of individuals making movements did however differ between biotopes. Movement in the power line corridor was only made in relatively shorter ranges, opposite to what may be expected from a dispersal corridor, meaning that dispersal and movement in power line corridors may be closer to suitable habitats than dispersal corridors. This should be considered helpful to conservation efforts where dispersal and new habitats are important.